Implementation of Quality Function Deployment (QFD) in PT. Prosperous Pomegranate Aceh Singkil - Raudatun Sumi; Nur Ahmadi Bi Rahmani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The researchaims to find out more about the extent to which quality function deployment (QFD) is plemented in large or small companies in Indonesia. Especially in Aceh Singkil. QFD is know to be a tool that companies can use in the production process (services) by translating consumer desireng into the technical characteristics of the company. Then can help the product development team communicate with management abaout what they want to do, and show strategies for moving forward for the company’s progress.